Partnership of United State Agency for International Development and Transvestite Union of Surabaya City in the fight against HIV-AIDS 2014-2016 - Purnama Pangaribuan; Adiasri Putri Purbantina (Jurnal Sosiologi Dialektika, 2022)
The HIV/AIDS epidemic in the city of Surabaya is a concern for the community, especially for transvestite in the city of Surabaya. In 2015, there were 933 HIV/AIDS cases recorded. The purpose of this research is to analyze the role of NGOs with local communities in tackling HIV-AIDS and how to access health care for transvestite in their environment. This study uses qualitative analysis methods through literature analysis and in-depth interviews with several representatives from the Surabaya City Transvestite Association (Perwakos). The results of the study show that the widespread stigma against homosexuality in society makes transwomen or transvestite groups experience significant obstacles, especially in obtaining quality health care and services. In addition, the lack of access to the necessary health services is one of the obstacles faced by transvestite groups, even though access to HIV-AIDS treatment for transvestite groups is very much needed. This can be overcome through treatment programs, counseling on the dangers of HIV-AIDS and multi-sectoral coordination between Perwakos, USAID and community groups. Cooperation with various parties is expected in advancing shared health priorities. This includes supporting the vision of the Government of Indonesia in realizing an effective and efficient national health service program.